Disease mutant analysis identifies a new function of DAXX in telomerase regulation and telomere maintenance - Tang, Mengfan (J Cell Sci, 2015)
Most human cancers depend on the telomerase to maintain telomeres; however, about 10% of cancers are telomerase negative and utilize the alternative lengthening of telomeres (ALT) mechanism. Mutations in the DAXX gene have been found frequently in both telomerase-positive and ALT cells, and how DAXX mutations contribute to cancers remains unclear. We report here that endogenous DAXX can localize to Cajal bodies, associate with the telomerase and regulate telomerase targeting to telomeres. Furthermore, disease mutations that are located in different regions of DAXX differentially impact on its ability to interact with its binding partners and its targeting to Cajal bodies and telomeres. In addition, DAXX knockdown by RNA interference led to reduced telomerase targeting to telomeres and telomere shortening. These findings collectively support a DAXX-centric pathway for telomere maintenance, where DAXX interaction with the telomerase regulates telomerase assembly in Cajal bodies and telomerase targeting to telomeres.